Clinicopathological factors influencing the number of stages of Mohs surgery for basal cell carcinoma - Joana Calvão; André Pinho; Ana Brinca; Ricardo Vieira (Sociedade Brasileira de Dermatologia, 2022)
Abstract Background Mohs Micrographic Surgery (MMS) is commonly used to treat high-risk basal cell carcinoma (BCC). Objectives Correlate clinicopathologic preoperative features with the number of MMS stages (primary endpoint) and margins (secondary endpoint) required for BCC complete excision. Methods We retrospectively analyzed BCCs treated by MMS in a 2-year period at the study's institution. Variables studied included the patient gender, age, immune status, lesion size, location, if it was a primary, recurrent, or persistent tumor, histopathologic characteristics, number of surgical stages, and amount of tissue excised. Results 116 BCCs were included. The majority (61.2%, n = 71) required a single-stage surgery for complete clearance, requiring a final margins of 3.11 ± 2.35 mm. Statistically significant differences between locations in different high-risk areas (periocular, perioral, nose, ear) and the number of MMS stages required for complete excision (p = 0.025) were found, with periocular tumours requiring the highest mean of stages (2.29 ± 0.95). An aggressive histopathology significantly influenced the number of MMS stages (p = 0.012). Any significant relation between clinicopathological features and variation in the final surgical margins was found, just certain tendencies (male patients, persistent tumor, periocular location, and high-risk histopathological tumors required larger margins). Neither patient age or tumor dimension correlated significantly with both number of MMS stages and final surgical margins. Study limitations Limitations of this study include its single-center nature with a small sample size, which limits the value of conclusions. Conclusion Main factors related to a greater number of MMS stages were periocular location and high-risk histopathological subtype of the tumor.